2004
DOI: 10.1021/ma049515r
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Study of Poly(ethylene tetrafluoroethylene) (Tefzel) by Hyperthermal Atomic Oxygen

Abstract: In this study the erosion of poly(ethylene tetrafluoroethylene) (ETFE) (Tefzel) by hyperthermal atomic oxygen (AO) has been examined using X-ray photoelectron spectroscopy (XPS). Initially, the Tefzel film had F/C and O/C atom ratios of 0.74 and 0.04, which decrease to 0.17 and 0.01, respectively, after a 2 h exposure to a flux of 2 × 1015 atoms/(cm2 s) AO with an average kinetic energy of 5 eV. The F/C atom ratio is further reduced to 0.02 with longer AO exposures, essentially producing a graphitic or amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…The two commonly used techniques for simulating the atomic oxygen found in LEO are: a) hyperthermal or fast atomic oxygen [69][70][71], and b) oxygen plasma [11,55]. In this study the oxygen plasma method, provided by the facility at NASA Glenn, was utilized using an electron cyclotron resonance (ECR) plasma source to produce neutral atomic oxygen.…”
Section: Atomic Oxygen and Vacuum Uv Radiation Effectsmentioning
confidence: 99%
“…The two commonly used techniques for simulating the atomic oxygen found in LEO are: a) hyperthermal or fast atomic oxygen [69][70][71], and b) oxygen plasma [11,55]. In this study the oxygen plasma method, provided by the facility at NASA Glenn, was utilized using an electron cyclotron resonance (ECR) plasma source to produce neutral atomic oxygen.…”
Section: Atomic Oxygen and Vacuum Uv Radiation Effectsmentioning
confidence: 99%
“…The inhomogeneous distribution of functional grafted sites in the PEMs takes responsibility for the poor‐quality conductance at the low GDs (≤20%), while the surface fractures take place at the higher GDs 42,43 . To our knowledge, there have been very limited attentions on the chemical compositions and their distribution at the surface layers of graft‐type PEMs, 11–13,15,16,19–21,41,44–46 although such a topic is one of the primary steps toward an understanding of its degradation behavior 19–21,33,41–43,46 . In addition, all previous studies on the chemical compositions and distributions on the surface of graft‐type PEMs have been limited to GDs ≤ 50% (IECs ≤ 2.2 mmol/g) 11,12,15,16,19–21,44 .…”
Section: Introductionmentioning
confidence: 99%
“…The amount of O 2 that chemisorbs provides a measure of the concentration of reactive sites in the near‐surface region. Previous studies have shown that AO‐exposed Kapton,11 Tedlar,43 and Tefzel44 chemisorb very large amounts of molecular oxygen, and this indicates that these surfaces contain a high concentration of reactive sites. These reactive sites are probably present because cross bonding cannot occur on account of geometrical constraints.…”
Section: Resultsmentioning
confidence: 94%